Neuromuscular adaptations to training, injury and passive interventions: Implications for running economy - Bonacci, J.; Chapman, A.; Blanch, P.; Vicenzino, B. (Sports Medicine, 2009)
Performance in endurance sports such as running, cycling and triathlon has long been investigated from a physiological perspective. A strong relationship between running economy and distance running performance is well established in the literature. From this established base, improvements in running economy have traditionally been achieved through endurance training. More recently, research has demonstrated short-term resistance and plyometric training has resulted in enhanced running economy. This improvement in running economy has been hypothesized to be a result of enhanced neuromuscular characteristics such as improved muscle power development and more efficient use of stored elastic energy during running. Changes in indirect measures of neuromuscular control (i.e. stance phase contact times, maximal forward jumps) have been used to support this hypothesis. These results suggest that neuromuscular adaptations in response to training (i.e. neuromuscular learning effects) are an important contributor to enhancements in running economy. However, there is no direct evidence to suggest that these adaptations translate into more efficient muscle recruitment patterns during running. Optimization of training and run performance may be facilitated through direct investigation of muscle recruitment patterns before and after training interventions.